The Impact of Google Gemini Artificial Intelligence–Assisted Instruction on Students’ Paragraph Writing Ability - Yuliani, Sri; Mardatillah, Annisa; Shalawati, Shalawati; Hartanto, Dicki; Masrul, Masrul; Dwiyanti, Lisa (Journal of English Language and Education, 2026)
The increasing use of artificial intelligence (AI) in language education has drawn significant attention to its potential to support students’ writing development. This study investigates the impact of Gemini AI–assisted instruction on students’ paragraph writing ability using a one-shot case study experimental design. Gemini AI was integrated into the instructional process for undergraduate students enrolled in a paragraph writing course. Following the intervention, 28 students completed a post-test in the form of a paragraph writing task. Their writing was evaluated using an analytical scoring rubric focusing on coherence, organization, vocabulary use, grammatical accuracy, and unity. The findings indicate that Gemini AI provided effective scaffolding during the writing process, as students demonstrated satisfactory to strong performance, particularly in organization, idea development, and coherence. Although the one-shot design limits causal interpretation due to the absence of a pre-test and control group, the results offer initial empirical evidence of the pedagogical potential of Gemini AI in paragraph writing instruction. The study therefore recommends further research using more rigorous experimental designs and highlights the importance of integrating AI tools in a careful and pedagogically informed manner.